Integrating techno-economic analysis into restoration ecology: bridging ecological outcomes with financial feasibility - Ayompe, Lacour M. (Frontiers in Sustainability, 2026)
Restoration ecology has become a critical discipline for addressing biodiversity loss, climate change, and ecosystem degradation. Yet, many restoration initiatives struggle to scale due to uncertain financial feasibility and limited integration of economic analysis into ecological planning. Techno-economic analysis (TEA), widely applied in energy and industrial systems, offers a structured framework for evaluating restoration interventions by combining technical performance metrics with cost-effectiveness and life-cycle economics. In this integrative review, I examine the role of TEA in restoration ecology to bridge ecological outcomes with financial viability. Drawing on examples from the literature of forest restoration, peatland rewetting, blue carbon ecosystems, and urban green infrastructure, the analysis reveals that TEA is particularly effective for optimizing high-capital, active restoration interventions, though less distinct in passive regeneration contexts. This review illustrates that while TEA enhances the transparency, comparability, and scalability of restoration projects, it also presents significant governance challenges, including regional data disparities, the risk of “carbon tunnel vision,” and ethical concerns regarding the commodification of nature. I argue that integrating TEA into restoration ecology can strengthen investment decisions and support Payments for Ecosystem Services (PES) schemes, provided it is coupled with robust safeguards to ensure equitable outcomes. Ultimately, by systematically linking ecological and economic dimensions, TEA provides a powerful decision-support tool for designing resilient strategies capable of meeting the dual imperatives of conservation and climate adaptation.